Asymmetrical Response of the East Asian Summer Monsoon to the Quadrennial Oscillation of Global Sea Surface Temperature Associated With the Tibetan Plateau Thermal Feedback. Issue 20 (14th October 2020) - Liu, Senfeng; Duan, Anmin; Wu, Guoxiong
Abstract: The leading mode of the global sea surface temperature anomaly (SSTA) on the interannual time scale is a quasi‐quadrennial oscillation mode, corresponding to the El Niño–Southern Oscillation cycle. Using observational data diagnosis and numerical simulations, we show that the global SSTA during the quadrennial cycle has significant impacts on the anomaly of diabatic heating over the Tibetan Plateau (TP) in summer. Idealized atmospheric general circulation model (AGCM) experiments forced by the global SSTA with and without the thermal forcing of the TP diabatic heating anomaly reveal the relative contributions of the SSTA direct effect and the TP feedback to the anomalous response of the East Asian summer monsoon (EASM). During the quadrennial oscillation, in the developing year summer, the diabatic heating weakens over the whole TP, inducing suppressed EASM precipitation accompanied by an anomalous cyclone over the northwestern Pacific and an anticyclone in North China. In the decaying year summer, the TP heating, characterized by an anomalous negative‐positive pattern, induces an anomalous anticyclone in South China and an anomalous cyclone in North China. However, without the anomalous TP thermal forcing, in both developing and decaying years the EASM shows similar response patterns with an anomalous anticyclone over the northwestern Pacific, an anomalous cyclone in North China, and an enhanced main rainfall band. Therefore, the TP thermal feedback plays a key role in the asymmetric responses of the EASM to the global SSTA during the different stages, characterized by suppressed precipitation in developing years and an enhanced main rainfall band in decaying years. Key Points: Quadrennial oscillation of global SST has different impacts on the Tibetan Plateau heating during summer in developing and decaying years The Tibetan Plateau thermal feedback in summer has effects on circulation and precipitation in East Asia during the quadrennial oscillation Global SST asymmetrically affects the East Asian summer monsoon mainly through the Tibetan Plateau thermal feedback effect